Entre campos de poder : think tanks e opinião pública - Juliana Cristina Rosa Hauck (2019)
Based on the notions that discourse engenders political change and that public opinion is a significant factor in pressuring such changes, this thesis is dedicated to explaining how organizations recognized as think tanks in Brazil structure their modus operandi to increase their potential of influence on public opinion. We used a relational theoretic- conceptual framework, whose core lies in the relations established by the organization specially with four fields of power: media, politics, knowledge production and business. Observing the distancing and approaching dance of the organizations to these fields – assessing which experts they recruit and which partners they relate – we seek to explain the levels of potential influence on public opinion of the cases analyzed. We studied 10 cases of which 04 have a pro market ideological profile, 03 are undefined ideologically and other 03 have a progressive profile. This diversity enabled a proper comparative analysis and more generalized conclusions. We found that the combinations of distancing and approximation of the fields of power used by organizations with progressive and undefined profile generated lower potentials of influence on public opinion than those used by organizations with a pro market profile. Beyond the theoretical-conceptual implications and the projection of a think tank research agenda, these results become very relevant when we look at the contributions of these pro market organizations to the “war of ideas” in politics, that ultimately impacted the recent elections results and the boards of governamental decision makers.